2014
DOI: 10.1364/oe.22.012982
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel terahertz time-domain spectroscopy system at 1030 nm excitation wavelength

Abstract: We present Terahertz (THz) imaging with a 1D multichannel time-domain spectroscopy (TDS) system which operates with a photoconductive array of 15 detection channels excited by a 1030 nm femtosecond fiber laser. The emitter and detector are photoconductive antennas based on InGaAs/InAlAs multi-layer heterostructures (MLHS). We characterized the THz optics and the resolution of the system. The performance is demonstrated by the multichannel imaging of two samples. A simultaneous measurement of 15 THz pulses with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…For the terahertz regime, this can be accomplished by three possible ways. First, having an array of photoconductive antennas [70][71][72], however this approach suffers from antenna cross-talk and inefficiency problems arising from the small working-area of the antennas whilst occupying a large area. Further, such antennas arrays have only been used as detectors.…”
Section: Spatially Patterned Thz Generationmentioning
confidence: 99%
“…For the terahertz regime, this can be accomplished by three possible ways. First, having an array of photoconductive antennas [70][71][72], however this approach suffers from antenna cross-talk and inefficiency problems arising from the small working-area of the antennas whilst occupying a large area. Further, such antennas arrays have only been used as detectors.…”
Section: Spatially Patterned Thz Generationmentioning
confidence: 99%
“…They further increased the number of antenna elements to 128 (1-D) in the following work [39]. In 2014, Brahm et al, demonstrated the fabrication of a 1D PCA array (15 antenna elements) [40] using InGaAs/InAlAs multi-layer heterostructure substrate for the excitation wavelength of 1030 nm. All these works show that the fabrication of multipixel PCA array is promising for the development of high-speed THz imaging system.…”
Section: Introductionmentioning
confidence: 99%
“…Large external biases are essential for increasing a peak THz power leading to restrictions on photoconductors, namely on its carrier relaxation times and resistance. The ternary compound InGaAs is a promising photoconductor since it operates with long-wave laser pump 1.0−1.55 µm emitted by fiber lasers that allows for fabricating low-cost and compact THz emitters for THz spectroscopy and imaging [15], [16]. When an ultrafast laser pulse with photon energy above the semiconductor bandgap strikes InGaAs, electron-hole pairs are generated at sub-surface of the semiconductor.…”
Section: Introductionmentioning
confidence: 99%